A high performance self-healing strain sensor with synergetic networks of poly(ɛ-caprolactone) microspheres, graphene and silver nanowires. (7th July 2017) - Liu, Shuqi; Lin, Yong; Wei, Yong; Chen, Song; Zhu, Jiarong; Liu, Lan
Abstract: Flexible strain sensors have been widely applied in wearable devices. However, few studies focus on the self-healing performance though this property is essential to practical applications due to the inevitability of irreversible mechanical damages/cracks in the reciprocating deformation. Here we report a simple and effective approach to fabricate a flexible strain sensor with a conductive composite layer by pouring liquid polydimethylsiloxane (PDMS) on the hybrids of poly(ɛ-caprolactone) microspheres (m-PCL), graphene oxide (GO) and silver nanowires (AgNWs). Through a multidimensional hybridization method, the hybrid fillers form a synergetic conductive network in which GO have good interactions with both m-PCL and AgNWs, thus covering m-PCL and anchoring AgNWs. Due to the synergetic effects of the m-PCL/GO/AgNWs (PGA) conductive network, the strain sensor shows high sensitivity (0.26 rad −1 ), good conductivity (0.45 S/cm), excellent durability (more than 2400 bending cycles) and outstanding repeatable self-healing property at moderate temperature (self-healed for more than 5 times at 80 °C in 3 min), ensuring the potential applications in wearable devices.